Integration of biochar and Bradyrhizobium japonicum modulates soil physicochemical properties and microbial community in soybean fields - Aziz, Sikandar; Bi, Yilong; Rehman, Faizur; Ibrahim, Muhammad; Rasheed, Syed Majid; Khan, Shahid; Wang, Chengyu; Liu, Shuxia (Frontiers in Plant Science, 2025)
Declining soil fertility and reduced microbial diversity due to intensive farming threaten sustainable agriculture. This study aimed to assess the effects of B. japonicum inoculation and biochar amendment, applied individually and in combination, on soil properties, microbial communities, and soybean yield under field conditions in Jilin Province, China. A field experiment was established with four treatments: control (CK), B. japonicum alone (RH), biochar alone (CK2), and their combination (RHB). Observations were recorded at flowering (FS), seed-filling (SFS), and harvesting (HS) stages. Soil physicochemical properties, microbial diversity, and soybean yield were evaluated to determine treatment responses. The RHB treatment significantly improved soil fertility. Soil pH increased from 5.77 in CK to 6.20 in RHB, total nitrogen rose from 0.12% to 0.19%, and available phosphorus increased from 32.4 to 45.3 mg/kg. Available potassium and soil organic matter increased by 18.2% and 27.7%, respectively. Soybean yield was highest in RHB (3798 kg/ha) compared to CK (3158 kg/ha) and correlated strongly with total nitrogen (TN) (r = 0.84), nitrate nitrogen (r = 0.75), and available nitrogen (r = 0.67). Microbial analysis revealed enrichment of beneficial genera, including Pseudomonas and Beauveria, along with higher populations of nitrogen-cycling bacteria and mycorrhizal fungi, thereby enhancing nutrient cycling. B. japonicum inoculation combined with biochar significantly enhanced soil fertility, improved microbial diversity, and increased soybean yield, offering a sustainable strategy to strengthen soil health and productivity in intensive farming systems.